The Mediating Role of Purchase Interest in the Influence of Green Marketing and Religiosity on Starbucks Product Purchase Decisions - Irfan Sunanto; Moh Farhan Ramadan; Khusnul Koiril Badriah; Aang Curatman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to ascertain if purchase interest can mediate the relationship between green marketing and religiosity and purchase decisions, as well as the impact of both on purchasing decisions. Data analysis is the research methodology employed in this study, with a focus on users who actively purchase products from Starbucks. The sample size of 144 persons was chosen using a purposive sampling technique; the population number is unknown. In this study, the SEM-PLS approach was employed, and SmartPLS 4 was utilized for data processing. The study's findings show that: Green marketing influences purchase interest; religion has no effect on purchase interest; religious beliefs have an impact on purchase decisions; and purchase interest has an impact on purchase decisions. Purchase Interest affects decisions about purchases; it also mediates the impact of green marketing on decisions about purchases; however, it does not mediate the impact of religiosity on decisions about purchases.